Measurement of Left Atrial Volume from Transthoracic Three-Dimensional Echocardiographic Datasets Using the Biplane Simpson’s Technique - Iwataki, Mai; Takeuchi, Masaaki; Otani, Kyoko; Kuwaki, Hiroshi; Haruki, Nobuhiko; Yoshitani, Hidetoshi; Tamura, Masahito; Abe, Haruhiko; Otsuji, Yutaka (Journal of the American Society of Echocardiography, 2012)
Although left atrial volume (LAV) by two-dimensional (2D) echocardiography provides prognostic information, the misalignment of the 2D cutting plane of the left atrium could make the measurements inaccurate. The aim of this study was to test the hypothesis that LAV measurement from three-dimensional (3D) echocardiographic data sets using the biplane Simpson’s technique is a more reliable approach for measuring LAV. The accuracy of 3D echocardiographic LAV measurements was retrospectively determined in 20 patients using multidetector computed tomography as a reference. LAV indexed to body surface area (LAVI) was measured using 2D and 3D echocardiography in 200 other subjects. LAV determination by 2D echocardiography was performed using the biplane Simpson’s method. A 3D determination of LAV was performed using quantitative software and the biplane Simpson’s method using the anterior-posterior and medial-lateral 2D views extracted from the 3D data sets. Although LAV using the 3D volumetric method (mean, 98 ± 24 mL) was slightly but significantly lower than LAV on multidetector computed tomography (mean, 103 ± 23 mL), a significant correlation between the two methods (r = 0.97, P < .001) with acceptable limits of agreement was noted. The left atrial short-axis image extracted from the 3D data sets revealed an ellipsoid shape. Although a good correlation for LAVI was noted between the 2D biplane Simpson’s method and the 3D volumetric method (r = 0.96, P < .001), the mean value of 2D echocardiographic LAVI was significantly greater compared with 3D echocardiographic LAVI, with a mean bias of 4.7 mL/m2. An excellent correlation was noted between the 3D biplane Simpson’s and 3D volumetric methods (r = 0.99, P < .001), with a lower bias (0.54 mL/m2) and limits of agreement of ±5.8 mL/m2. The time required for LAV analysis was significantly shorter with the 2D (mean, 82 ± 7 sec) and 3D (mean, 94 ± 11 sec) biplane Simpson’s methods (P < .01 vs 2D biplane Simpson’s method) compared with the 3D volumetric methods (mean, 135 ± 24 sec) (P < .01 vs 2D and 3D biplane Simpson’s methods). The 2D biplane Simpson’s method overestimates LAV because of the misalignment of the 2D cutting plane, and the 3D biplane Simpson’s method is a practical and more reliable way to accurately determine LAV.